Baseline data on abundance, site fidelity and association patterns of common bottlenose dolphins (Tursiops truncatus) off the northeastern Tunisian coast (Mediterranean Sea) - Benmessaoud, R.; Cherif, M.; Bejaoui, N. (J. Cetacean Res. Manage., 2023)
The common bottlenose dolphin has been studied intensively in numerous locations around the world but very little is known about this species along the South Mediterranean Basin. In this study, the temporal distribution of dolphins, group dynamics, site fidelity and association patterns of common bottlenose dolphins along the northeastern coastal waters of Tunisia was assessed through mark-recapture photo-identification techniques. Prior to this study, no research has focused on bottlenose dolphins within these waters, despite the potential for human impacts on this species. A total of 718h of boat-based observations, spanning 284 days, were spent at sea between August 2008 and July 2010. During this period, 253h were spent in direct observation of 317 groups of common bottlenose dolphins. Bottlenose dolphins were observed in all seasons, although seasonality was evident, with more encounters during the summer. Photo-identification studies show that 43 individuals used the northeastern coast of Tunisia on a regular basis, while others were present less often. Based on a social structure analysis it was possible to discriminate different communities related with the spatial distribution of the sightings (Zembra island, Hammamet, Kelibia and Galite island).